Caracterização hematológica e bioquímica de puérperas - impactos no filho recém-nascido - Rodrigues, Keila Thais Passos Martins (2020)
An analysis of the umbilical cord blood count has the advantage of avoiding vascular puncture in the newborn, thus reducing the risk of infection. It is known that maternal hematological and biochemical parameters may differ when compared to their specific newborns. Therefore, it is important to assess the impact of maternal laboratory and sociodemographic data on newborns. Objective: To characterize laboratory data of postpartum women and umbilical cord blood of full-term and premature newborns and compare them to sociodemographic variables and laboratory data of postpartum women. Methodology: A cross-sectional observational study was carried out in 467 puerperal women, and their newborns, attended at the Maternidades Pública Alvorada and Instituto da Mulher Dona Lindu in the city of Manaus, from June 2017 to March 2019. Data sociodemographic clinics were obtained through a questionnaire and access to the medical records of the mothers. Hematological and biochemical data were acquired through analyzes performed on the peripheral venous blood of puerperal women and the umbilical cord of newborns. Results: As for the puerperal women, 379 (81.1%) declared themselves brown, 64.8% were attending or had completed high school, most were married (76.4%) and the average age was 20, 1 ± 6.4. Normal delivery occurred in 53.5% of births. Triglyceride levels were proportionate to advancing gestational age at delivery. The absolute number of leukocytes was higher in those puerperal women between 12 and 15 years old and male newborns had a high elevated transferrin, while female newborns had a high MCV and HCM. Conclusion: Our results show that the status of iron and hemoglobin may not be associated with each other when it appears in umbilical cord blood. Furthermore, we observed important differences in hematological parameters when associated with spontaneous abortion. We understand that the knowledge of the hematological and biochemical profile of pregnant women and their respective newborns can contribute to minimize neonatal morbidity and mortality, as well as generate subsidies for further studies in the context of qualifying prenatal care